2018
DOI: 10.1021/acsomega.8b01576
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin as a Nanotransporter for Glabridin: Exploring the Binding Properties and Bioactivity Influences

Abstract: Based on the fact that β-lactoglobulin (β-lg) can solubilize readily in water and bind many small hydrophobic molecules, a novel nanocomplexed glabridin with β-lg was developed by an antisolvent precipitation method. After binding to β-lg, the solubility of glabridin in aqueous solution was enhanced 21 times. Fluorescence spectroscopy of β-lg revealed that the interaction of glabridin with β-lg made the environment of Trp and Tyr residues on β-lg more hydrophilic. The morphology and crystal form of the nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The binding constant K a and binding site values of and n were found to be 4.69 x 10 5 L mol -1 and 1.3, respectively, from the double logarithmic plot (Figure 2c). The n value suggests that there is a one-to-one interaction in the binding site of BLG, the binding constant values are on the order of 10 5 M −1 , and there is a strong binding affinity in the BLG-AMA complex (11) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The binding constant K a and binding site values of and n were found to be 4.69 x 10 5 L mol -1 and 1.3, respectively, from the double logarithmic plot (Figure 2c). The n value suggests that there is a one-to-one interaction in the binding site of BLG, the binding constant values are on the order of 10 5 M −1 , and there is a strong binding affinity in the BLG-AMA complex (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were taken at 282 nm with different AMA concentrations, where [Q] corresponds to the molar concentration of AMA. Based on the linear plot, it can be concluded that there is 1:1 complexation in the BLG-AMA system (11) . The binding constant K b was calculated to be 2.9 x 10 4 L mol -1 at pH 7.4 (298 K) by dividing the intercept by the slope (Figure 1 (c)).…”
Section: Absorption Spectral Studymentioning
confidence: 97%
See 2 more Smart Citations
“…The clinical application of glabridin is limited due to its poor water solubility and therefore low bioavailability, but studies have shown that this situation can be improved by combining it with β -Lactoglobulin. ( Wei et al, 2018 ). These results indicate the potential of glabridin in OA prevention and treatment as a potential drug for OA.…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%